Self-assembled block copolymer micelles with silver–carbon nanotube hybrid fillers for high performance thermal conduction. Issue 5 (19th December 2014) - Choi, Jae Ryung; Yu, Seunggun; Jung, Haejong; Hwang, Sun Kak; Kim, Richard Hahnkee; Song, Giyoung; Cho, Sung Hwan; Bae, Insung; Hong, Soon Man; Koo, Chong Min; Park, Cheolmin
Abstract : A novel, polymer-filled composite with thermal conductivity of 153 W m −1 K −1 was developed by the blending block copolymer micelles, MWNTs and deformable Ag particles. Abstract : The development of polymer-filled composites with an extremely high thermal conductivity (TC) that is competitive with conventional metals is in great demand due to their cost-effective process, light weight, and easy shape-forming capability. A novel polymer composite with a large thermal conductivity of 153 W m −1 K −1 was prepared based on self-assembled block copolymer micelles containing two different fillers of micron-sized silver particles and multi-walled carbon nanotubes. Simple mechanical mixing of the components followed by conventional thermal compression at a low processing temperature of 160 °C produced a novel composite with both structural and thermal stability that is durable for high temperature operation up to 150 °C as well as multiple heating and cooling cycles of Δ T = 100 °C. The high performance in thermal conduction of our composite was mainly attributed to the facile deformation of Ag particles during the mixing in a viscous thermoplastic medium, combined with networked carbon nanotubes uniformly dispersed in the nanoscale structural matrix of block copolymer micelles responsible for its high temperature mechanical stability. Furthermore, micro-imprinting on the composite allowed for topographically periodic surface micropatterns, which offers broader suitability for numerous micro-opto-electronic systems.